Echocardiographic evidence of concentric left ventricular enlargement in female weightlifters - George, K. P.; Batterham, A. M.; Jones, B. (European Journal of Applied Physiology, 1998)
In this study we investigated resting left ventricular structure and function in elite female weightlifters.The female weight-lifters demonstrated a concentric left ventricular enlargement that was not detrimental to left ventricular performance at rest.